Problems Of Learning Islamic Education at Junior High School: Problematika Pembelajaran Pendidikan Agama Islam di SMP Negeri 2 Tarik Sidoarjo - Elya Muslimatul Istiqomah; Ainun Nadlif (Academia Open, 2022)
This article aims to analyze the problems of learning Islamic education at SMP Negeri 2 Tarik Sidoarj, so as to find out the problems of learning Islamic education at SMP Negeri 2 Tarik Sidoarjo and provide solutions to the problems of learning Islamic education at SMP Negeri 2 Tarik Sidoarjo. This study uses a qualitative research data obtained from the field. The results of this study show that, (1) The learning process of Islamic Religious Education at SMP Negeri 2 Tarik Sidoarjo is still not running stably or not optimally, (2) The problem that occurs in learning Islamic Religious Education at SMP Negeri 2 Tarik Sidoarjo is the lack of student understanding. on the material provided by the teacher, low student motivation, there are still many students who are not fluent in reading the Qur'an in accordance with Tajweed, and perform the 5 daily prayers regularly. The problem with educators is the lack of competence in mastering the class and lack of competence in mastering learning materials, (3) Efforts made on the Problems of Learning Islamic Religious Education at SMP Negeri 2 Tarik are additional lessons and the inclusion of Reading and Writing the Qur'an (BTQ) in additional subjects, making student diaries containing prayer schedules for 5 times, the school will provide guidance and involve teachers, especially teachers of Religious Education I slams.